2023
DOI: 10.3390/su15053872
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Management and Total Quality Management Impact on Employee Effectiveness in Emerging Industries: Case of Tunisian Small and Medium Enterprises

Abstract: Employee effectiveness is highly important for all economic activities. Several factors can affect its degree, either positively or negatively. In this vein, this work aims to examine the impact of knowledge management and total quality management on employee effectiveness in the industry of emerging countries. For that, Tunisian small and medium enterprises were taken as an example. The proposed methodology consists first of providing a research model linking the correlation between knowledge management eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…These findings are consistent with Lynch and Jin's (2016) and Chung et al's (2019) results that the ability of knowledge creation may expand the knowledge base and increase the network actors' performance. In their study, Lehyani et al (2023) assert the significance of knowledge transfer in enhancing employee effectiveness. This process relies on sharing tacit and explicit employee knowledge within an organization, leading to the generation, design, and development of more brilliant ideas.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are consistent with Lynch and Jin's (2016) and Chung et al's (2019) results that the ability of knowledge creation may expand the knowledge base and increase the network actors' performance. In their study, Lehyani et al (2023) assert the significance of knowledge transfer in enhancing employee effectiveness. This process relies on sharing tacit and explicit employee knowledge within an organization, leading to the generation, design, and development of more brilliant ideas.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding healthcare field, Dagasan et al(2023)pointed out that TQM principles produce different performance outcomes like the job performance of employees. Furthermore, Lehyani et al(2023) studied the impact of knowledge management and TQM impact on employee effectiveness in Emerging Industries in the case of Tunisian Small and Medium enterprises(SMEs) and they confirmed that there is a positive and significant relation between TQM practices application and employee effectiveness determinents. In summary, it is remarkable that TQM and staff effectiveness have mutual relationships based on the intersection of their practices.…”
Section: Introductionmentioning
confidence: 85%
“…TQM enables each employee to have the chance to engage, serve and establish a sense of ownership and responsibility [50]. Many studies have been conducted on the implementation of TQM, and it is considered that the advantages of increased customer satisfaction, higher-quality goods, and increased market share are frequently acquired after the deployment of TQM by construction organisations [51,52]. According to [53], people-related TQM becomes essential for both universities and people-related TQM practices.…”
Section: Total Quality Managementmentioning
confidence: 99%